Prenatal Diagnosis of Fragile X: Can a Full Mutation Allele in the FMR1 Gene Contract to a Normal Size? - Manor, Esther; Jabareen, Azhar; Magal, Nurit; Kofman, Arei; Hagerman, Randi J.; Tassone, Flora (Frontiers in Genetics, 2017)
Here we describe a case of a prenatal diagnosis of a male fetus that inherited the unstable allele from his full mutation mosaic mother (29, 160, >200 CGG repeats) reduced to a normal size range (19 CGG repeats). Haplotype analysis showed that the fetus 19 CGG repeats allele derived from the maternal unstable allele which was inherited from his maternal grandmother. No size mosaicism was detected by testing the DNA from in vitro cultured samples, including 7th passage culture as well as from two amniocentesis samples. Sequence analysis confirmed that the allele was 19 CGG repeats long. Methylation assay showed no methylation. Although none of the techniques used in this study can provide with absolute certainty the diagnosis, the results strongly indicate the presence in the fetus of an allele with a CGG repeat number in the normal range. Because this is a prenatal diagnosis case, the crucial question is whether the 19 CGG allele derived from the maternal unstable expanded allele, which contracted to the normal range, became a normal stable allele or a normal unstable allele which could expand in the next generation. It is also possible that allele size mosaicism of the FMR1 gene that went undetected exists. Because this is a prenatal diagnosis case, we cannot with certainty exclude the presence of an undetected expanded allele of the FMR1 gene, in addition to the 19 CGG allele derived from an unstable expanded allele, which contracted to the normal range.